Criminal Law Policy on the Protection of Protected Wildlife - Lesmana, Wiyata Yudha; Abduh, Rachmad (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2024)
Indonesia has biodiversity and ecosystems that are so very important that protection of conservation is needed because there are many crimes against ecosystems and the environment for endangered species. This research raises the issue of the rule of law on protecting protected wildlife in Indonesia and legal efforts in protecting protected wildlife. This study aims to answer the problems that become the issue of research discussion, namely examining criminal law policies in wildlife protection in Indonesia. The method used in this study is normative juridical, which examines the literature on legislation (library research). The study results show that the government's legal regulations, policies, and laws that strengthen the factors aimed at protecting wildlife in Indonesia are very good. However, the lack of public awareness is caused by economic factors or insufficient food needs, resulting in actions prohibited by the government and laws, namely hunting and illegal trade.